The Concept of Wahdah Al-Wujud: Comparative Study on Sheikh Siti Jenar and Mulla Shadra’s Perpertives - Nurus Syarifah (State Islamic Institute of Manado (IAIN) Manado, Indonesia, 2022)
This article explains the comparison of the concept of wahdah al-wujud between Siti Jenar and Mulla Sadra. Siti Jenar is famous for the idea of her divine ontology, which is always interesting to discuss; Manunggaling Kawula Gusti. In contrast, Mulla Sadra is famous for the concept of his ontology called al-Hikmah al-Muta’aliyyah. This study uses a type of library research with descriptive analytical methods. The results show that the concept of wahdah al-wujud between Siti Jenar and Mulla Sadra has similarities and differences. The similarities and differences between the two focus on the form of God and His creatures. As for the similarities, both assume the form of God and His creatures are the same. However, the difference lies in the cause of being